Rancang Bangun Antena Bowtie pada Video Sender sebagai Pemancar TV Streaming (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Negeri Semarang, 2018)
A streaming television usually broadcasted through internet and can be watched on computer or mobile phone. However it can also be seen through television using video sender as the transmitter. To transmit it, of course, a suitable antenna is needed, in this case a bowtie antenna is selected. This research describe the design of a bowtie antenna that will be used as a transmitter antenna on a video sender. This bowtie antenna is designed by using an aluminum plate works on frequency of 655 MHz and has a return loss value of -21.127 dB, VSWR 1.192, 5.11 dB gain and bi-directional radiation pattern. The analysis process is carried out by analyzing the data taken from the audio and video results received in television as well as data from the measurement of signal strength captured by Register Transfer Level Software Define Radio (RTL SDR) and dipole antennas. Measurement results will be displayed in the sdrSharp software. The results of this measurement will be associated with field strength which is related to television signals. This bowtie antenna can transmit audio and video up to 30 m and has an average field strength value in Line of Sight (LOS) conditions of 120.3208 dBÎ¼V / m and at Non Line of Sight (NLOS) conditions of 123.5014 dBÎ¼V / m which is in accordance with the field strength standard in Indonesia that regulated in Perkominfo No. 31 Tahun 2014 which is above 70 dBÎ¼V / m in band V.